The failed amnesty of the ‘years of lead’ in Italy: Continuity and transformations between (de)politicization and punitiveness - Rossi, Federica (European journal of criminology, 2023)
The ?years of lead? commonly refer in Italy to the decade of the 1970s, characterized by widespread conflictuality, the use of violence for political aims and harsh state repression of political activism. Political violence has been primarily handled with both normal and exceptional means of criminal justice, yet debates on amnesty and reconciliation have been recurrent over the years. This article traces the history of the debates on amnesty and pardon for politically motivated offences to show how they have been shaped by changing national and international contexts. On the one hand, the ?failed amnesty? reflects the long-lasting repressive approach adopted by the Italian state to address the question of the political violence in the 1970s and the reluctance to acknowledge its collective and political character. On the other hand, this article argues that, beyond the apparent continuity of a punitive approach, the gradual disappearance of amnesty from political debates in the 1990s?2000s is symptomatic of a more paradigmatic shift resulting from the combination of different factors and trends, such as the transformation of the Italian political landscape in the early 1990s, the emergence and affirmation of a new punitive discourse, as well as the increasing delegitimation of amnesties in transitional settings. Thus, through a specific case-study, this article draws links between criminal justice and penal trends, political transformations and developments in transitional justice, and consequently intends to contribute to the discussion of the concept of punitiveness and the effects of the expanding international criminal law on the treatment of politically motivated offences.